Thermodynamics properties of C24 and C24O5 cluster molecules using The Density Functional Theory - Khalaf, Taif Talib; Hussein, Mohammed T. (Iraqi Journal of Science, 2026)
Electronic characteristics density of state, density of bonds, and the thermodynamic characteristics (Gibbs Energy, Enthalpy, Entropy, and Heat Capacity) of coronene hydrogen bare C24 and reduced coronene oxide C24O5 were investigated with the variation of temperature between (298 – 398) K. The hybrid functional B3LYP (Becke, 3-parameters, Lee-Yang-Parr) with 6-311G** basis sets was employed in Density Functional Theory (DFT). It was found that the value of the energy gap of coronene hydrogen bare C24 was 3.5 eV, while it decreased for reduced coronene oxide C24O5 to 1.38 eV due to adding levels inside the energy gap. The theoretical values of bond length were 1.38 Å for the C=C bond and 1.22 Å for the C=O bond, which were in good agreement with experimental results. An exergonic reaction was indicated by a decrease in the Gibbs energy (in a negative sign) as the temperature rise. Entropy, heat capacity, and enthalpy all increased in value with temperature.